Legal Protection of Women and Children in Isbat Marriage accompanied by Divorce - Achmad Walif Rizqy; Ishaq, Ishaq; Muhammad Faisol (Journal of Law, Politic and Humanities, 2024)
Until now, it is felt that the marriage ceremony accompanied by divorce has not provided complete justice, especially in terms of applications by women. When women apply, their rights are often neglected, especially when the verstek decision means that the rights of women and children are lost. In this research, the focus is on discussing the rights of women and children in marriage isbat cases accompanied by divorce and forms of legal protection for women and children in marriage isbat cases accompanied by divorce. The research method in this research uses a normative/doctrinal type of research which focuses on the legal issue being researched and uses two approaches, namely the statutory approach and the conceptual approach. This research results in discussion that women and children in cases of isbat marriage accompanied by divorce actually have many regulations that regulate them to protect their rights, but are sometimes neglected because the law cannot reach far in ensuring justice is present in them, especially in the context of legal protection, especially Repressive legal protection does not yet describe a just situation that substantively guarantees the basic rights of women and children. Even though the regulations have been regulated in such a way, the implementation does not show justice, especially in cases filed by women.